On the advisability of using antioxidants in the treatment of acute salpingooophoritis - T. A. Marziyeva; I. E. Rogozhina; T. N. Glukhova (Лечащий Врач, 2021)
The study of the state of lipid peroxidation processes in patients with acute salpingo-oophoritis, as well as the rationale for the use of antioxidant therapy in the complex treatment of patients with this pathology, was carried out. In a group of 50 patients with acute salpingooophoritis, traditional treatment was performed, including antibacterial agents in accordance with the clinical protocol for the diagnosis and treatment of pelvic inflammatory diseases (2015), anti-inflammatory, detoxification therapy (comparison group). In 50 patients with acute salpingo-oophoritis, similar complex therapy was supplemented by the appointment of drugs with antioxidant properties (main group). When patients were admitted to the hospital and after therapy, the state of lipid peroxidation processes in the blood was assessed by the content of lipid hydroperoxides and malondialdehyde in blood plasma and in red blood cells, as well as the state of the antioxidant blood system. The results of the studies indicate the activation of lipid peroxidation and the destabilization of biological membranes in patients with acute salpingo-oophoritis. It is shown that the use of antioxidant therapy in the complex treatment of patients with acute salpingooophoritis helps to reduce the treatment time in the hospital and improves the long-term results of treatment for patients with this pathology.